'I'm not Catholic and I'm not Protestant': Identity, individualisation and challenges for history education in Northern Ireland. Issue 2 (19th October 2021) - Branford, Abigail
Abstract : page_126 other Teaching sensitive histories in post-conflict societies makes particular demands on educators to understand students' identities and their relationships to the past. This paper expands our understanding of post-conflict youth identities and experiences of history education through a small-scale study of students' life stories in Northern Ireland which defied sectarian boundaries in different ways: some were children of interfaith marriages, while others attended integrated schools or were part of cross-community peace-building organisations. Participants saw themselves as forging new identities and 'moving on' from the past, although this process was fraught with ambivalence. I describe these expressions of identity through Ulrich Beck's (1992) model of triple individualisation. For these 'post-sectarian' students, school history was seen largely as a tool towards achieving qualification, far removed from their everyday struggles of self-fashioning.